2023
DOI: 10.1002/hep.32686
|View full text |Cite
|
Sign up to set email alerts
|

Direct chemical induction of hepatocyte‐like cells with capacity for liver repopulation

Abstract: Background and Aims: Cell fate can be directly reprogrammed from accessible cell types (e.g., fibroblasts) into functional cell types by exposure to small molecule stimuli. However, no chemical reprogramming method has been reported to date that successfully generates functional hepatocyte-like cells that can repopulate liver tissue, casting doubt over the feasibility of chemical reprogramming approaches to obtain desirable cell types for therapeutic applications.Approach and Results: Here, through chemical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In recent years, new methods and cell sources have been developed, including direct chemical-induced hepatocyte-like cells, induced pluripotent stem cell-derived liver organoids directed by engineering gene regulatory networks, and direct reprogramming of endothelial cells. 15 17 These potential alternative hepatocytes have provided a novel platform for studying the molecular mechanisms in the liver and developing therapeutic strategies for liver diseases. Despite these advances in the development of hepatocyte sources, many difficulties are encountered when inducing fully mature hepatocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new methods and cell sources have been developed, including direct chemical-induced hepatocyte-like cells, induced pluripotent stem cell-derived liver organoids directed by engineering gene regulatory networks, and direct reprogramming of endothelial cells. 15 17 These potential alternative hepatocytes have provided a novel platform for studying the molecular mechanisms in the liver and developing therapeutic strategies for liver diseases. Despite these advances in the development of hepatocyte sources, many difficulties are encountered when inducing fully mature hepatocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Single-cell sequencing has found significance in cancer research, microbiology, in vitro fertilization, neurobiology, and developmental biology. 9,10 Comprehensive characterization of proteome, lipids, and metabolites can provide phenotyping information, which can be used for investigation of cell functions, differentiation, and signal pathways. 11 Mass spectrometry (MS) has become a powerful tool for the measurement of proteins, lipids, and metabolites in single cells, which shows advantages such as high efficiency, fast speed, low cost, high detection sensitivity, and accuracy.…”
mentioning
confidence: 99%
“…Advances in DNA and RNA sequencing technology have made it possible to analyze genome and transcriptome in single cells. , Single-cell sequencing has found significance in cancer research, microbiology, in vitro fertilization, neurobiology, and developmental biology. , Comprehensive characterization of proteome, lipids, and metabolites can provide phenotyping information, which can be used for investigation of cell functions, differentiation, and signal pathways . Mass spectrometry (MS) has become a powerful tool for the measurement of proteins, lipids, and metabolites in single cells, which shows advantages such as high efficiency, fast speed, low cost, high detection sensitivity, and accuracy. , Although MS-based single-cell profiling of proteins, metabolites, or lipids has been reported, it still remains challenging for multi-omics analysis in single cells.…”
mentioning
confidence: 99%
“…For instance, the study by Bai et al, [5] in this issue of Hepatology, represents an important proof of concept in the field of liver cell reprograming. In the study, a small molecule cocktail in the culture media was shown to directly reprogram mouse embryonic and neonatal skin fibroblasts into functional iHeps with the capability to repopulate mouse livers in vivo (Figure 1).…”
mentioning
confidence: 99%